Prevalence of hepatitis C virus co-infection in adults living with HIV in Mexico: a cross-sectional, seroprevalence study in a nationally representative sampleResearch in context - Pablo F. Belaunzarán-Zamudio; Juan L. Mosqueda-Gómez; J. Oggún Cano-Torres; Claudia Guillén-López; Teresa Muñoz-Trejo; Kenia Escobedo-López; Alejandro Rivera-Marroquín; Akio Murakami-Ogasawara; José L. Sánchez-Bello; Margarita M. Rosas-Dossetti; Elizabeth Papaqui-Limón; Alethse De la Torre-Rosas; et al. (The Lancet Regional Health. Americas)
Summary: Background: The proportion of people living with HIV (PLWHIV) co-infected with HCV in Mexico was unknown. Our aim was to estimate the seroprevalence of HCV among adults with HIV in Mexico. Methods: Using a complex-survey design, we collected blood samples and applied structured questionnaires between May 2nd, 2019 and February 17th, 2020 in a nationally, representative sample of adults receiving care for HIV-infection in 24 randomly selected HIV-care centres in 8 socio-demographically regions in Mexico. We tested serum for anti-HCV IgG antibodies and collected data on risky exposures. We estimated the seroprevalence of HCV and associated exposures using regression models and the Taylor linearization method to account for the cluster effect by region and centre. Findings: We collected blood samples of 2545 participants. Most participants were men (75.8%) with a median age of 37 years. The estimated seroprevalence of HCV is 3.9% (95% CI 3.1%–4.7%). Only 39 of 99 participants (40%) with HCV antibodies had active replication determined by RNA quantification. Seroprevalence of HCV was significantly higher among people with life-time history of imprisonment (9%, 95% CI 4.4%–13.6%), tattoo use (5.9%, 95% CI 3.9%–8%), and lifetime (22.3%, 95% CI 12.1%–32.6%) and recent (49.3%, 95% CI 18.3%–80.3%) injecting-drug use. Interpretation: Seroprevalence of HCV infection among PLWHIV in Mexico is ten times as high as the seroprevalence for the general population. The national program for HCV elimination focused in PLWHIV should target people that use injecting drugs and living in prisons. Funding: Abbvie Farmacéuticos, S.A de C.V Mexico through Investigator Initiated Study (2018).